Detonation Spraying of Hydroxyapatite on a Titanium Alloy Implant - Natalia V. Bulina (Materials, 2021)
Hydroxyapatite (HA), the major mineral component of tooth enamel and natural bones, is a good candidate for bone tissue engineering. Synthetic HA is used for making coatings on metallic implants intended for medical applications. A HA coating renders the implant biocompatible and osteoinductive. In addition, it improves fixation and the overall performance of the implanted object. In the present work, HA coatings were deposited on a medical titanium alloy implant with mesh geometry and a developed surface by detonation spraying. The feedstock powder was HA obtained by the dry mechanochemical method. Single-phase HA coatings were obtained. The coatings were formed not only on the surfaces normal to the particle flow direction, but also on the sides of the mesh elements. Despite partial melting of the powder, no decomposition of HA occurred. This work demonstrates the prospects of detonation spraying for the production of HA coatings on metallic implants with complex geometries.